Behavior of MnS inclusions during homogenization process in low-alloyed steel FAS3420H - Liu Shuai (De Gruyter, 2021)
Sulfur is added to low-alloyed steel FAS3420H to improve the free-cutting property of the steel. Elongated MnS inclusions usually deteriorate the mechanical and process performance of steels, so the control of shape and size of MnS is essential. The statistical analysis of MnS inclusions in as-cast and rolled steels at different positions shows that the distribution and aspect ratio of MnS in rolled steel are closely related to the quantity and size of MnS in as-cast one. The in situ observation and experimental results reveal that homogenization treatment effectively reduced MnS inclusions size and transformed their shape to globule or ellipsoid. Significant change of quantity and size of MnS inclusions was identified only when the soaking time exceeds 5 h at 1,250℃. Additionally, a kinetic model is presented to quantitatively characterize the behavior of MnS inclusions during homogenization process.